2019
DOI: 10.5039/agraria.v14i3a6363
|View full text |Cite
|
Sign up to set email alerts
|

Application of thermogravimetric analysis as a pre-selection tool for Eucalyptus spp.

Abstract: The aim of the study was to evaluate the use of thermogravimetric analysis in the pre-selection of genetic materials. Twenty-five Eucalyptus spp. genetic materials were used. The analysis of the data consisted of three stages; first, was carried out an exploratory study of the wood and charcoal properties. Subsequently, a Pearson correlation analysis was performed between the parameters of thermogravimetric analysis (TGA) and the properties of wood and charcoal. Finally, once the presence of significant correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…It was observed that in the range of 100 to 200°C there was no mass loss for the diff erent studied clones. This range is known as the wood thermal stability zone (Fialho et al, 2019). Yang et al (2007) studying the thermal degradation of wood constituents, observed hemicellulose weight loss occurring mainly at 220 -315°C and cellulose at 315 -400°C, similar to what was found in this study.…”
Section: Thermal Properties Of Woodsupporting
confidence: 87%
See 3 more Smart Citations
“…It was observed that in the range of 100 to 200°C there was no mass loss for the diff erent studied clones. This range is known as the wood thermal stability zone (Fialho et al, 2019). Yang et al (2007) studying the thermal degradation of wood constituents, observed hemicellulose weight loss occurring mainly at 220 -315°C and cellulose at 315 -400°C, similar to what was found in this study.…”
Section: Thermal Properties Of Woodsupporting
confidence: 87%
“…In fact, the mean value observed in the present study for the holocellulose content was 65.6%. Fialho et al (2019), in turn, found more intense degradation between 300 and 450°C. The less accentuated peak corresponds to the higher degradation rate of hemicelluloses, whose mean degradation range was from 222 to 297°C and is related to an average mass loss of 18% between 200 and 300°C.…”
Section: Thermal Properties Of Woodmentioning
confidence: 87%
See 2 more Smart Citations
“…The genetic materials in this study, all presented a high charcoal yield (Fialho et al 2019;Carneiro et al 2016;Pereira et al 2013). However, this propriety by itself isn't enough for genetic materials selection.…”
Section: Discussionmentioning
confidence: 79%